Effect Of Cigarette Smoking On Blood Sodium And Potassium Levels In Sudanese Subjects - EMAD-ALDIN I. OSMAN; ABDULLAH A. DAFALLAH; WALEED H. OMER; GAMAL M. ELIMIRI (International Journal of Pharma and Bio Sciences, 2011)
This study aimed to investigate the effect of cigarette smoking on plasma sodium and potassium levels. Atomic emission flame spectrophotometry was used to measure plasma sodium and potassium in sixty subjects, thirty smokers and thirty non-smokers as matched controls. The plasma sodium and potassium were analyzed before and after smoking in the smokers, while the analysis was done once in non-smoker cohort. There was a significant increase in sodium level immediately after smoking among smokers (p < 0.05) and no significant change in potassium level. No change was found in plasma sodium level between smokers (before smoking) and non-smokers. In addition, there is a decrease in plasma potassium level among smokers (before smoking) in comparison to non-smokers; however, it is statistically not significant. This study reveals that cigarette smoking has an immediate increasing effect on plasma sodium level. It is recommended that cigarette smoking should be avoided especially before blood sodium measurement.